Cashew nut allergy; immune health challenge. (April 2019) - Tufail, Tabussam; Saeed, Farhan; Ul Ain, Huma Bader; Niaz, Bushra; Afzaal, Muhammad; Din, Ahmad; Rasul Suleria, Hafiz Ansar
Abstract: Background: Cashew nut allergy is a significant tree nut allergy that is increasing gradually and becoming serious health issue these days. Allergens responsible for cashew nut allergy are highly potent and for some people, these reactions have the potential to be severe and even life-threatening (anaphylaxis). Increased consumption of cashew nuts and a change in eating and cooking may be responsible. It's time to spread the knowledge and awareness about cashew nut allergy among society, clinics and development of clinical confession. Scope and approach: In recent era, various researches regarding cashew nut allergy are under consideration. In this comprehensive review, investigations were carried to identify aspects of cashew nut allergy including its prevalence, characteristics, processing effects, different allergens, diagnosis and management. Key findings and conclusion: Main etiology is the utilization of minor quantity of cashew nut allergens like Ana-o-3, Ana-o-1 and Ana-o-2, proposed to be very powerful as compared to other tree nuts. Its prevalence is increasing especially in children. Several methods like oral immunotherapy, adrenaline auto-injector device and enzymatic processing are very helpful in the treatment of this emerging type of allergy. Moreover, labelling of foods products having cashew nuts plays significant role in prevention of cashew nut allergy. This information concludes that allergen of cashew nut allergy may be powerful that is chronic cause of many immune disorders. Highlights: Encouraging awareness in public for cashew nut allergy. Highlighting prevalence of cashew nut allergy. Evaluating epidemiology of cashew nut allergy. Revealing diagnosis methods and management of cashew nut allergy.